A comprehensive characterization of cell cultures and xenografts derived from a human verrucous penile carcinoma - Muñoz, Juan J. [UNESP]; Drigo, Sandra A. [UNESP]; Kuasne, Hellen [UNESP]; Villacis, Rolando A. R.; Marchi, Fabio A.; Domingues, Maria A. C. [UNESP]; Lopes, Ademar; Santos, Tiago G.; Rogatto, Silvia R. [UNESP] (Springer Nature, 2016)
This study aimed to establish and characterize primary cell cultures and xenografts derived from penile carcinoma (PeCa) in order to provide experimental models for cellular processes and efficacy of new treatments. A verrucous squamous cell carcinoma (VSCC) was macrodissected, dissociated, and cultivated in KSFM/DF12 medium. Cell cultures were evaluated at passage 5 (P5) using migration and invasion assays and were serially propagated, in vivo, in BALB/c nude mice until passage 3 (X1–X3). Immunophenotypic characterization of cultures and xenografts was performed. Genomic (CytoScan HD, Affymetrix) and transcriptomic profiles (HTA 2.0 platform, Affymetrix) for VSCC, cell cultures, and xenografts were assessed. P5 cells were able to migrate, invade the Matrigel, and produce tumors in immunodeficient mice, demonstrating their malignant potential. The xenografts unexpectedly presented a sarcomatoid-like carcinoma phenotype. Genomic analysis revealed a high similarity between the VSCC and tumor-derived xenograft, confirming its xenograft origin. Interestingly, a subpopulation of P5 cells presented stem cell-related markers (CD44+CD24− and ALDH1high) and sphere-forming capacity, suggesting their potential xenograft origin. Cell cultures and xenografts retained the genomic alterations present in the parental tumor. Compared to VSCC, differentially expressed transcripts detected in all experimental conditions were associated with cellular morphology, movement, and metabolism and organization pathways. Malignant cell cultures and xenografts derived from a verrucous penile carcinoma were established and fully characterized. Nevertheless, xenograft PeCa models must be used with caution, taking into consideration the selection of specific cell populations and anatomical sites for cell/tumor implantation.
Keywords: Experimental disease models; Mice; Neoplasms; Penile neoplasm; Primary cell cultures